sin3x−cosxcos2x=√2(tan2x+2tanx−1)1−tanx2 (1)
Điều kiện: {cosx≠0cos2x≠0tanx≠±1 ⇔ {x≠π2+kπx≠π4+kπ2 (k∈Z)
Nhân tử và mẫu của VP cho cos2x, ta được:
(1)⇔sin3x−cosxcos2x=√2(sin2x+2sinxcosx−cos2x)cos2x−sin2x
⇔sin3x−cosxcos2x=√2(2sin2x−cos2x)cos2x
⇔sin3x−cosx=√2(2sin2x−cos2x)
⇔cos(π2−3x)−cosx=2sin(2x−π4)
⇔−2sin(π4−x)sin(π4−2x)=−2sin(π4−2x)
⇔sin(π4−2x)=0∨sin(π4−x)=1
∗sin(π4−2x)=0⇔2x−π4=kπ⇔x=π8+kπ2(k∈Z)
∗sin(π4−x)=1⇔π4−x=π2+k2π⇔x=−π4−k2π(k∈Z)
So với điều kiện, ta suy ra nghiệm của phương trình là: x=π8+kπ2(k∈Z)